TRANSFORMASI MEDIA KOMUNIKASI TAHURI DARI PENANDA BUDAYA HINGGA KE PENANDA MUSIKAL - Mentari Cklaudita Walalayo (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2025)
This study aims to understand the phenomenon of the transformation of Tahuri, a traditional medium of communication, from a cultural symbol into a musical symbol within the social life of the Hutumuri community. The analysis of this phenomenon is linked to auditory perception, musical creativity, and the collective memory of the community. To support this analysis, several theoretical frameworks are employed. The concepts of Victor Turner and Maurice Halbwachs are utilized to examine the emergence of the idea and conceptual transformation of Tahuri through the reflective experiences of its initiators. Auguste Comte’s sociological perspective is used to understand the social construction of the new function of Tahuri as a musical instrument within the Hutumuri community. Furthermore, the theories of Andrew Gregory and Djohan are applied to explore the influence of music on the community’s enthusiasm for preserving Tahuri as cultural heritage. To achieve these objectives, this research adopts a qualitative approach, using semi-structured interviews with eight informants who are directly involved in the use and preservation of Tahuri. The findings of this study indicate that the transformative idea of Tahuri originated from the reflective experiences of its initiators, who recognized both the musical and cultural potentials inherent in the instrument. This idea was positively received by the Hutumuri community, who also acknowledged Tahuri’s musical potential and considered that its use as a musical instrument does not interfere with its function as a cultural symbol. Therefore, transforming Tahuri into a musical instrument represents an effective strategy to foster the enthusiasm of the Hutumuri community in preserving Tahuri. The productivity of musical activities and the optimization of performance quality have contributed to the personal development of Tahuri musicians, enabling their active participation in musical activities at the Sanggar Kakoya Tahuri Hutumuri.